The Juridical Analysis of the Institutional Relationship between the Financial Services Authority and Bank Indonesia Related to the Bank's Soundness Level - Widodo Ramadhana Widodo Ramadhana (Ilmu Hukum Prima (IHP), 2021)
Under Article 7 of the Financial Services Authority Act, the Financial Services Authority declares that the Financial Services Authority has the authority to regulate and supervise the Bank's institutions which include licensing for establishment of a bank. In this Coordination Protocol as a forum for reconciliation between the Ministry of Finance, Bank Indonesia, the Financial Services Authority and the Deposit Insurance Corporation in a coordination forum called the Financial System Stability Committee (KSSK). Coordination in this committee is made if it is not possible to handle banking problems by the Financial Services Authority in relation to the settlement and handling of a failed bank that is suspected to have a systemic impact. The Financial Services Authority also requires the controlling shareholders or investors to increase the capital of the Systemic Bank and be able to convert the type of debt or investment to increase the capital of the systemic bank if faced with potential crisis.